A comparison of air-conditioning system in intelligent building with conventional building / Abdul Hamid Abdul Multalib - Abdul Multalib, Abdul Hamid (Faculty of Architecture, Planning and Surveying, 2010)
Air-conditioning system must provide both cooling and dehumidification to maintains comfort in the building. Maintenance management of air-conditioning system is very important for safety and comfort as well as retaining the market value of the property. The problem of air-conditioning system must avoid from occur because to maximize the operation of the building. This report is important to me as student as it provides me with hands on experience and basic knowledge before commencing work in the future. I have learnt a lot of beneficial things such as air-conditioning system use in building, how to maintain the comfort in buildings and what is the problem air conditioning systems occurred. The topic are covered in this report is airconditioning system in building, maintenance management, the problem of air-conditioning system and comparison of air-conditioning system in intelligent building with conventional building.